2004
DOI: 10.1074/jbc.m312452200
|View full text |Cite
|
Sign up to set email alerts
|

Human Amylin Oligomer Growth and Fibril Elongation Define Two Distinct Phases in Amyloid Formation

Abstract: Human amylin (hA), a 37-amino-acid polypeptide, is one of a number of peptides with the ability to form amyloid fibrils and cause disease. It is the main constituent of the pancreatic amyloid deposits associated with type 2 diabetes. Increasing interest in early assembly intermediates rather than the mature fibrils as the cytotoxic agent has led to this study in which the smallest hA oligomers have been captured by atomic force microscopy. These are 2.3 ؎ 1.9 nm in height, 23 ؎ 14 nm in length, and consist of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

21
125
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(151 citation statements)
references
References 37 publications
21
125
2
Order By: Relevance
“…Human amylin's physiological conformation is one of random coil, but it undergoes rapid conformational change into β-conformers when placed in physiological solutions [35]. Based on the available evidence, many workers have concluded that small oligomers formed by aggregated human amylin [36,37] are probably the species that could ultimately cause diabetes [38,39]. Others, among them Zraika and colleagues, believe that the cytotoxicity of larger amyloid fibrils must be considered [11,15], as indeed it must.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Human amylin's physiological conformation is one of random coil, but it undergoes rapid conformational change into β-conformers when placed in physiological solutions [35]. Based on the available evidence, many workers have concluded that small oligomers formed by aggregated human amylin [36,37] are probably the species that could ultimately cause diabetes [38,39]. Others, among them Zraika and colleagues, believe that the cytotoxicity of larger amyloid fibrils must be considered [11,15], as indeed it must.…”
mentioning
confidence: 99%
“…Oligomers are now known to form spontaneously in human amylin solutions, among and often concomitantly with the larger, precipitable fibrillar structures that have typically been visualised by electron microscopy [26]. Amylin oligomers, which are usually at least two orders of magnitude smaller than fibrils, are initially a few nm in diameter [37]. Application of real-time atomic force microscopy (AFM) has enabled measurement of their dimensions, mass and time-dependent growth [36,37].…”
mentioning
confidence: 99%
See 3 more Smart Citations